The Politics of Nuclear Energy in the European Union : Framing the Discourse : Actors, Positions and Dynamics - Barnes, Pamela M., 1950-; Barnes, Ian, 1945- (Barbara Budrich Publishers, 2018)
For the foreseeable future, the overall use of nuclear electricity in the European Union is unlikely to change significantly despite the controversies surrounding its use among the EU's nation states. The authors question the role that nuclear electricity plays in meeting the challenges of providing secure, competitive, and sustainable energy to support the development of the low carbon economy in the EU. Analysis presented focuses on the evolution of the discourse on nuclear energy among policy makers at European and national levels as well as the public.